Differential Geometry explained easily: A new teaching concept - Gunesch, Roland (Gesellschaft für Didaktik der Mathematik, 2012)
This article describes a new method to teach differential geometry in a way which is more intuitive, more appealing to students, and which can help students to better understand crucial concepts of differential geometry.
Beiträge zum Mathematikunterricht; 46, 2012
Keywords: 510